Keterampilan Proses Sains dan Berfikir Tingkat Tinggi Siswa melalui Model Inductive Thinking dan Group Investigation - Siska Aidarahmi; Binari Manurung; Diky Setya Diningrat (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to determine the science process and high-level thinking of class X high school students who are given an inductive thinking and group investigation learning model. This research was carried out in April-June at MAN 1 Aceh Tenggara. The research population was all class X MIA students of 300 people. The sample was taken by purposive sampling and amounted to 60 people. The research results show that (1) There is a very significant difference in science process skills and learning models. The results of science process skills taught using the investigative group learning model (88.83 ± 8.37) were more significant than the inductive thinking learning model (85.50 ± 7.23); (2) There is a very significant difference between high level thinking and learning models. The results of higher level thinking taught using the investigative group learning model (87.33 ± 13.37) were more significant than the inductive thinking learning model (83.33 ± 12.41); (3) There are differences in science process skills given the inductive thinking learning model and group investigation at low and high KBA; (4) There are differences in high-level thinking given the inductive thinking learning model and group investigation at low and high KBA; (5) There is a relationship between science process skills and students' higher level thinking from the results of applying the inductive thinking learning model and group investigation, r = 0.876 and r^2 = 0.768.